Staging Memory: The Drama Inside the Language of Elfriede Jelinek - Gita Honegger (Studies in 20th & 21st Century Literature, 2007)
This essay focuses on Jelinek's problematic relationship to her native Austria, as it is reflected in some of her most recent plays: Ein Sportstück (A Piece About Sports), In den Alpen (In the Alps) and Das Werk (The Plant). Taking her acceptance speech for the 2004 Nobel Prize for Literature as a starting point, my essay explores Jelinek's unique approach to her native language, which carries both the burden of historic guilt and the challenge of a distinguished, if tortured literary legacy. Furthermore, I examine the performative force of her language. Jelinek's "Dramas" do not unfold in action and dialogue, rather, they are embedded in the grammar itself. Her radically subversive vision of Austrian culture reveals her own deep roots in it and the obsessive longing to align herself with its purest and martyred voices—from Hugo von Hofmannsthal to Paul Celan. Against the exploitation by contemporary tourism of a landscape that is riddled with the undead of political and commercial crimes, against the pollution and perversion of official language, Jelinek's linguistic experiments, destructive and anti-traditional at first sight, are urgently conservative projects.